2016
DOI: 10.3949/ccjm.83a.15065
|View full text |Cite
|
Sign up to set email alerts
|

Anemia of chronic kidney disease: Treat it, but not too aggressively

Abstract: Anemia of renal disease is common and is associated with significant morbidity and death. It is mainly caused by a decrease in erythropoietin production in the kidneys and can be partially corrected with erythropoiesis-stimulating agents (ESAs). However, randomized controlled trials have shown that using ESAs to target normal hemoglobin levels can be harmful, and have called into question any benefits of ESA treatment other than avoidance of transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 116 publications
0
35
0
1
Order By: Relevance
“…EPO is a glycoprotein hormone with a molecular mass of 30.4 kDa composed of a single 165 amino acid residues chain to which four glycans are attached (3). EPO is primarily produced by peritubular interstitial cells in the deep cortex and outer medulla of kidneys of the adult and in hepatocytes in the fetus (21). These cells are sensitive to hypoxia and once they are sensed, it leads to an increased EPO production (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPO is a glycoprotein hormone with a molecular mass of 30.4 kDa composed of a single 165 amino acid residues chain to which four glycans are attached (3). EPO is primarily produced by peritubular interstitial cells in the deep cortex and outer medulla of kidneys of the adult and in hepatocytes in the fetus (21). These cells are sensitive to hypoxia and once they are sensed, it leads to an increased EPO production (22).…”
Section: Discussionmentioning
confidence: 99%
“…If these components are lacking for a prolonged time, erythropoiesis and biosynthesis of haemoglobin slows and anaemia may result (2, 24). Anaemia is a common finding in patients with CKD and is primarily due to reduced production of erythropoietin in the kidney and shortened red cell survival (21).…”
Section: Discussionmentioning
confidence: 99%
“…Standard anemia treatment in CKD patients involves the administration of recombinant human erythropoietin, including epoetin α and epoetin β, due to the fact that a decrease in erythropoietin production in the kidneys is the key reason which underlines anemia [91]. Continuous erythropoiesis receptor activators which are a pegylated form of recombinant human erythropoietin with extended serum half-life allowing for longer dosing intervals (every 2 weeks) is currently gaining popularity in the community of dialysis patients [92]. Generally, the initial doses of epoetin-alfa or epoetin-beta dosing are from 20 to 50 IU/kg body weight three times a week.…”
Section: Anemia Treatment With Esamentioning
confidence: 99%
“…No differences were found in the abovementioned parameters between high and low hemoglobin groups [93]. However, three large randomized controlled trials (The Normal Hematocrit Study (NHCT) [90], The Correction of Hemoglobin and Outcomes in Renal Insufficiency (CHOIR) trial [94], and The Trial to Reduce Cardiovascular Events with Aranesp Therapy (TREAT) [18] demonstrated that establishing and reaching higher hemoglobin targets may be harmful to patients [92]. The re-analysis of results obtained in two large trials (CHOIR and the Cardiovascular Risk Reduction by Early Anemia Treatment (CREATE)) trials revealed that patients who despite receiving higher doses did not achieve their target hemoglobin had worse outcomes [95,96].…”
Section: Anemia Treatment With Esamentioning
confidence: 99%
“…1 A common complication of CKD is anemia associated with reduced erythropoietin (EPO) activity, iron deficiency, and inflammation. 2,3 Anemia is present in >90% of dialysis patients 4 and contributes to excess morbidity and mortality. 5 Erythropoiesis-stimulating agents (ESAs), composed mainly of recombinant forms of EPO, are the only drugs approved internationally to treat severe anemia in patients with CKD.…”
mentioning
confidence: 99%